830-nm InGaAs Quantum Well Lasers With Very Low Beam Divergence - Bocang Qiu; Hai Martin Hu; Weimin Wang; James Ho; Wenbin Liu; Langxing Kuang; Taishan Wang; Shujuan Wu (IEEE Photonics Journal)
We report on our design and fabrication of 830-nm high-power semiconductor lasers with very low beam divergence. Here, we propose a novel approach in which by combining asymmetric waveguide and a feature called “pins” together, we were able to design an optimize epi structure, which not only produces a beam divergence of less than 16°, which is measured at the full width at the half maximum, but also has very good growth tolerance as well. Device test shows the beam divergence is as small as 13°, yet they still retain high slope efficiency of around 1.15 W/A and low threshold current of 400 mA for the devices with cavity length being 2 mm long, and ridge width being 40 μm wide.